Influence of substrates composition on immunomodulation by MSCs - Ferreira, Daniela Filipa Alves (2018)
Mesenchymal stem cells (MSCs) are non-hematopoietic multipotent stem cells capable to self-renew and differentiate along different cell lineages. MSCs can be found in adult tissues and extra embryonic tissues like the umbilical cord matrix/Wharton’s Jelly (WJ). The latter constitute a good source of MSCs, being more naïve and having a higher proliferative potential than MSCs from adult tissues like the bone marrow, turning them more appealing for clinical use. It is clear that MSCs modulate both innate and adaptive immune responses and its immunodulatory effects are wide, extending to T cells and dendritic cells, being therapeutically useful for treatment of immune system disorders. Mechanotransduction is by definition the mechanism by which cells transform mechanical signals translating that information into biochemical and morphological changes. Here, we hypothesize that by culturing WJ-MSCs on distinct substrates with different stiffness and biochemical composition, may influence the immunomodulatory capacity of the cells. Here, we showed that WJ-MSCs cultured on distinct PDMS substrates presented different secretory profiles from cells cultured on regular tissue culture polystyrene plates (TCP), showing higher secretion of several cytokines analysed. Moreover, it was also shown that WJ-MSCs cultured on PDMS substrates seems to possess higher immunomodulatory capabilities and to differentially regulate the functional compartments of T cells when compared to MSCs maintained on TCP. Taken together, our results suggest that elements of mechanotransduction seem to be influencing the immunomodulatory ability of MSCs, as well as their secretory profile. Thus, future strategies will be further explored to better understand these observation and to envisage new in vitro culture conditions for MSCs aiming at distinct therapeutic approaches, namely for immune-mediated disorders.